Pelvic Primary Staphylococcal Infection Presenting as a Thigh Abscess - T. O. Abbas (Case Reports in Surgery)
Intra-abdominal disease can present as an extra-abdominal abscess and can follow several routes, including the greater sciatic foramen, obturator foramen, femoral canal, pelvic outlet, and inguinal canal. Nerves and vessels can also serve as a route out of the abdomen. The psoas muscle extends from the twelfth thoracic and fifth lower lumbar vertebrae to the lesser trochanter of the femur, which means that disease in this muscle group can migrate along the muscle, out of the abdomen, and present as a thigh abscess. We present a case of a primary pelvic staphylococcal infection presenting as a thigh abscess. The patient was a 60-year-old man who presented with left posterior thigh pain and fever. Physical examination revealed a diffusely swollen left thigh with overlying erythematous, shiny, and tense skin. X-rays revealed no significant soft tissue lesions, ultrasound was suggestive of an inflammatory process, and MRI showed inflammatory changes along the left hemipelvis and thigh involving the iliacus muscle group, left gluteal region, and obturator internus muscle. The abscess was drained passively via two incisions in the posterior left thigh, releasing large amounts of purulent discharge. Subsequent bacterial culture revealed profuse growth of Staphylococcus aureus. The patient recovered uneventfully except for a moderate fever on the third postoperative day.